A review on the effect of laser pulse shaping on the microstructure and hot cracking behavior in the welding of alloys. (August 2021) - Zhang, Peilei; Jia, Zhiyuan; Yu, Zhishui; Shi, Haichuan; Li, Shaowei; Wu, Di; Yan, Hua; Ye, Xin; Chen, Jieshi; Wang, Fuxin; Tian, Yingtao
Highlights: According to the characteristics of pulsed laser, the application of pulsed laser in alloy welding was summarized. By discussing the crack sensitivity criterion, the mechanism of pulse laser welding to solve welding crack was analyzed. The outlook for the future trends of pulsed laser welding and crack criterion was presented. Abstract: There are mainly two kinds of laser used in welding of materials, continuous laser beam welding (CLBW) and pulsed laser beam welding (PLBW). The two kinds of laser welding have each welding characteristics. Compared with CLBW, the heat input of PLBW can be controlled lower, and has been widely used in the connection of thin plate materials. Since the pulse shaping can be edited to realize the preheating and slow cooling of each welding process, pulsed laser has been studied to suppress hot cracks and other defects in the field of aluminum alloy, magnesium alloy and other materials welding. This article describes the application of pulsed laser in alloy welding. The main welding problems and prevention methods were summarized. By discussing the index had been proposed to predict the sensitivity of solidification cracks, the formation and growth processes of hot cracks in pulsed laser welding was more comprehensively analyzed. Finally, the outlook for the future trends of pulsed laser welding is presented.